2018
DOI: 10.1007/s13105-018-0624-2
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for the link between defective autophagy and inflammation in peripheral blood mononuclear cells of type 2 diabetic patients

Abstract: Autophagy was shown to modulate inflammation in immune cells. This study was designed to evaluate the association between autophagy and inflammation in peripheral blood mononuclear cells (PBMCs) of type 2 diabetic (T2D) and non-diabetic (ND) subjects. The autophagy markers were measured by real-time PCR and western blot. The gene expression of pro- and anti-inflammatory cytokines was assessed by real-time PCR. Reduced transcription of BECN1 and LAMP2 and unchanged expression of MAP1LC3B and ATG5 were observed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 45 publications
1
11
0
2
Order By: Relevance
“…On the other hand, IL-10 exhibits beneficial metabolic effects (Donia et al 2016;Ip et al 2017). Our findings are similar to those of Alizadeh et al (2018) who revealed a lower mRNA expression of IL-10 in type 2 diabetic patients compared to non-diabetic subjects. Thus, reduced levels of serum IL-10 might lead to type 2 diabetes.…”
Section: Discussionsupporting
confidence: 89%
“…On the other hand, IL-10 exhibits beneficial metabolic effects (Donia et al 2016;Ip et al 2017). Our findings are similar to those of Alizadeh et al (2018) who revealed a lower mRNA expression of IL-10 in type 2 diabetic patients compared to non-diabetic subjects. Thus, reduced levels of serum IL-10 might lead to type 2 diabetes.…”
Section: Discussionsupporting
confidence: 89%
“…Our results coincide with several clinical studies that have been published, showing that Atg5, Atg8, and LC3 mRNA level were found to be largely reduced in the renal tissue of DN patients. 29,30…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, LAMP-2 down-regulation in PBMCs cultured with ASC EMS may be a novel mechanism that connects obesity and inflammation in EMS horses. It was shown that reduced autophagy in PBMCs in type 2 diabetes patients was correlated with an enhanced inflammation [ 36 ]. Therefore, it is tempting to speculate that rejuvenated ASCs with AZA/RES will affect the physiological properties of PBMCs after clinical application in EMS individuals by triggering autophagy, and, in consequence, diminishing the inflammatory state of the animal body.…”
Section: Discussionmentioning
confidence: 99%